The Influence of Green Marketing, Health Consciousness and Trust to E-Commerce toward Purchase Intentions for Health Mask Products in the Covid-19 Pandemic Era - Kukuh Prahesti; Sanaji Sanaji (Jurnal Ilmu Manajemen, 2022)
Changes that occurred due to the Covid-19 pandemic caused changes in people's consumption patterns. Environmentally friendly products are starting to appear, the increasing awareness of health and the shift from conventional trading activities to electronic commerce (e-commerce) require companies to quickly adapt and strategize along with these changes in an effort to increase consumer purchase intentions. This study aims to analyze the effect of green marketing, health consiousness, and trust to e-commerce on purchase intention toward MASNO product. This study involved 120 respondents, using non-probability sampling and judgmental sampling techniques. The questionnaires were distributed online through MASNO's Instagram account. Data analysis used multiple linear regression method. The results showed that green marketing and trust to e-commerce had significant effects on purchase intention toward MASNO, and health consciousness had no significant effect on purchase intention towards MASNO. The practical implication of this research is to increase consumers' purchase intention. One of the things that need to be considered is the impact of marketing activities on the environment, so that mask manufacturers are expected to be able to create innovative masks that are safe for consumers, safe for the environment, and interresting promotions. Integrity, priority to customers, and the ability of merchants to operate e-commerce platforms need to be improved so that it has an impact on increasing consumers’ purchase intention.